2016
DOI: 10.1158/2159-8290.cd-16-0297
|View full text |Cite
|
Sign up to set email alerts
|

MET-Driven Resistance to Dual EGFR and BRAF Blockade May Be Overcome by Switching from EGFR to MET Inhibition inBRAF-Mutated Colorectal Cancer

Abstract: A patient with metastatic BRAF -mutated colorectal cancer initially responded to combined EGFR and BRAF inhibition with panitumumab plus vemurafenib. Preexisting cells with increased MET gene copy number in the archival tumor tissue likely underwent clonal expansion during treatment, leading to the emergence of MET amplifi cation in the rebiopsy taken at progression. In BRAF -mutated colorectal cancer cells, ectopic expression of MET conferred resistance to panitumumab and vemurafenib, which was overcome by co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 29 publications
3
69
0
Order By: Relevance
“…Acquired resistance to RAF/EGFR inhibitor combination therapy is mediated by multiple genetic lesions(2931). In our work, we analyzed nine progression samples from patients and found that resistance was mediated by five different genetic aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired resistance to RAF/EGFR inhibitor combination therapy is mediated by multiple genetic lesions(2931). In our work, we analyzed nine progression samples from patients and found that resistance was mediated by five different genetic aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Another study coupling functional analysis and tissue genotyping revealed that MET amplification conferred resistance to the combination of panitumumab and vemurafenib in a BRAF-mutated CRC. In the same patient, a combination of vemurafenib with the dual ALK/MET inhibitor crizotinib was capable, even if temporarily, of overcoming resistance (130); interestingly, the choice was supported by pharmacologic analysis on a BRAF-mutant cell line made resistant to BRAF inhibition and showing emerging MET amplification. Similarly, in the study described by Crystal and colleagues, sequencing of patient samples alone was not sufficient for the prediction of effective combinations, suggesting that patient-derived avatars could also be exploited to functionally define patient-specific drug associations (109).…”
Section: Leveraging Biomarkers and Real-time Assessment Of Tumor Evolmentioning
confidence: 99%
“…MET exon 14 deletion has been postulated to be one potential mechanism for MET protein overexpression [93]. A recent study suggested MET amplification as a novel mechanism of the resistance to EGFR and BRAF combination blockade in BRAF -mutated CRCs; furthermore, the study showed that switching from EGFR to MET inhibition resulted in clinical response of the disease [94]. …”
Section: Molecular Testsmentioning
confidence: 99%